IDENTIFICATION AND SCREENING OF EXTRACELLULAR VIRULENCE FACTORS OF AEROMONAS SPP. IN ENVIRONMENTAL WATER SAMPLES FROM TAMILNADU, SOUTH INDIA - Indra, Umapathy; Geetha, Palaniswamy; Kumar, Balasubramanian Lakshman (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: Aeromonas species (spp.) are emerging pathogen that is present in drinking water supplies which are a major reason for public health concern. Factors contributing to virulence include toxins, haemolysins, adhesins and various hydrolytic enzymes. The present study aimed at investigating the incidence of Aeromonas spp. and its virulence factors from environmental water bodies in Coimbatore. Methods: A total of 180 water samples were collected and screened for the presence of pathogenic Aeromonas spp. using starch ampicillin agar. The conventional method of identification might lead to misidentification of Aeromonas spp. thus molecular based identification using 16S rRNA gene was carried out followed by the identification of production of extracellular virulence factors like haemolysin, gelatinase, caseinase, lipase and DNase. Results: Incidence of Aeromonas in water sample was found to be 55% (100 positive isolates) which was also confirmed with the molecular identification. The isolates showed 60% of haemolytic activity,, 34% of gelatinase activity, 77% of caseinase, 52% of lipase and 48% of DNase activity. Conclusion: This study, thus, provides valuable information for the existence of pathogenic Aeromonas spp. in the environmental water bodies. Use of such water for domestic and commercial purpose might lead to the transfer of the pathogenic Aeromonas spp. Keywords: Aeromonas spp, Haemolysis, Caseinase, DNase, Gelatinase and lipase.